مظاهر الاستيطان الفرنسي في الجزائر من بداية الاحتلال إلى قيام الجمهورية الفرنسية الثانية - طبعة, حورية (جامعة الوادي - University of Eloued, 2019)
The French generals who ruled Algeria since the occupation of the capital until the establishment of the Second Republic and beyond, did a colonial political in Algeria, they interested in keeping Algeria as a geopolitical location, exploiting its wealth, exporting French products to it, and settling the French and Europeans. The French authorities Inventory and confiscated the property of the Algerians by applying a series of different real estate laws in order to seize more land. They also resorted to other methods of looting, such as renting or Mock sale.
مقال
Keywords: الاحتلال؛ الاستيطان؛ الجمهورية الفرنسية؛ الجزائر